TO STUDY THE CHEMICAL COMPOSITION OF WOOLEN FABRIC - Amirova Toyiraxon Sheraliyevna (Journals Park Publishing, 2023)
Wool is characterized by a higher content of macronutrients than silk, i.e. 10125 and 6648 mg/kg, respectively. In the wool sample, the largest amount among the elements belongs to phosphorus (3790 mg/kg), and the smallest to magnesium (670 mg/kg). 17 trace elements were found in the wool sample. Iron has the highest content among microelements (484 mg/kg).
Keywords: wool, ash content, nitrogen, total protein, macro- and microelements, inductively coupled plasma mass spectrometer.